2015
DOI: 10.1007/s11547-014-0485-x
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative radiation dose and radiation risk from medical imaging in patients subjected to endovascular aortic aneurysm repair

Abstract: EVAR patients received high radiation doses and the excess cancer risk attributable to radiation exposure is not negligible. The unenhanced scan and the venous phase of the MDCT angiography could have been omitted without compromising the utility of the examination and with a significant reduction of doses and associated risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…154 Concerns have been raised about the possibility that late mortality after EVAR may be partly attributable to an increased late cancer burden due to external radiation exposure from the procedure itself or from stent-graft surveillance with CTA. 155 A recent population-based study suggests an increased risk of postoperative abdominal cancer after EVAR as compared with open AAA repair; however, within the EVAR group the use of CTA surveillance was not associated with any increased risk of postoperative abdominal cancer. 156 Conversely, other studies previously suggested that EVAR patients have an excess cancer risk attributable to cumulative external radiation exposure over time which is not negligible.…”
Section: Results and Follow-upmentioning
confidence: 90%
“…154 Concerns have been raised about the possibility that late mortality after EVAR may be partly attributable to an increased late cancer burden due to external radiation exposure from the procedure itself or from stent-graft surveillance with CTA. 155 A recent population-based study suggests an increased risk of postoperative abdominal cancer after EVAR as compared with open AAA repair; however, within the EVAR group the use of CTA surveillance was not associated with any increased risk of postoperative abdominal cancer. 156 Conversely, other studies previously suggested that EVAR patients have an excess cancer risk attributable to cumulative external radiation exposure over time which is not negligible.…”
Section: Results and Follow-upmentioning
confidence: 90%
“…Of 52 full-text publications examined (Figure 1), 22 articles 1,13 -33 were excluded based on exclusion criteria and an additional 3 articles 34-36 that could not be assigned to an equipment group because 2 articles 34,35 failed to report the type of C-arm (mobile or fixed) and 1 article 36 reported only the primary outcomes for a mixed group use of mobile and fixed C-arms. These latter 3 studies were excluded from the meta-analysis but were included in the overall correlation plot between FT and KAP (Supplementary Table S1; supplementary material available at http://jet.sagepub.com/content/by/supplemental-data).…”
Section: Resultsmentioning
confidence: 99%
“…Endovascular aneurysm repairs (EVARs) and thoracic endovascular aortic repairs (TEVAR) are fluoroscopically guided interventions that are accompanied by intraoperative radiation dose levels that are equipment, intervention, and complexity specific. 1 Most of the currently available C-arms used in (T)EVAR are the mobile (or portable) or fixed (angiosuite) versions. The mobile models are flexible C-arms that can easily be integrated into every operating room (OR), but they have limited image quality.…”
Section: Introductionmentioning
confidence: 99%
“…27 CTA has been recognised as the standard imaging modality following TEVAR, 7,27,28 and represents the best imaging to allow for standardisation of repeated aortic measurements, but CTA has also been associated with increased risk of radiation side effects. 39 The SVS guidelines recommend CTA imaging every two to five years in patients without imaging abnormalities at the 36 month radiology follow up, 7 instead of annual CTAs. A recent editorial published by EJVES proposed a revised surveillance protocol for BTAI patients after TEVAR.…”
Section: Discussionmentioning
confidence: 99%